Penerapan Model Pembelajaran Kolaboratif Untuk Peningkatan Hasil Belajar Muatan Pelajaran PPKn Dan Sikap Sosial Siswa Kelas II SD Negeri 1 Tumbu - Ni Ketut Sukadi (Cetta: Jurnal Ilmu Pendidikan, 2021)
This study aims to improve learning outcomes and social attitudes of second grade students in the odd semester of the 2017/2018 academic year through the application of a collaborative learning model in the content of Civics lessons. This research was conducted in two learning cycles. The learning model used in this study is a collaborative learning model. The object of research is social attitudes and student learning outcomes. To measure students' social attitudes, observational guidelines were used. To measure student learning outcomes used test learning outcomes. The data analysis used in this research is descriptive analysis. The results of data analysis showed that: 1) The application of the collaborative learning model can improve the learning outcomes of class II SD Negeri 1 Tumbu. There was an increase in student learning outcomes of Civics from the first cycle of 73.91 to the second cycle of 86.96 this indicates an increase in learning outcomes of Civics learning content of 17.65%. 2) The application of the collaborative learning model can improve the social attitudes of the second grade students of SD Negeri 1 Tumbu. The average value of students' social attitudes increased from 66.09 in the first cycle with the medium category to 80.96 in the second cycle with the high category. This indicates an increase in students' social attitudes by 22.50%. Learning outcomes in learning will be better if before carrying out the learning process prepare the required learning tools carefully and planned in advance in order to achieve the desired learning objectives.